2012
DOI: 10.1002/eat.22022
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal development predicts eating behaviors in adolescence

Abstract: Objective Early maturing girls are at increased risk for disordered eating. However, it is unclear if the association between puberty and disordered eating continues throughout pubertal development and if a similar association is exhibited in boys. Method Participants included 1340 same- and 624 opposite-sex twins from the Swedish Twin Study of Child and Adolescent Development. Pubertal development was assessed at age 13–14 with the Pubertal Development Scale. General disordered eating, measured with the Eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 120 publications
2
33
0
2
Order By: Relevance
“…With some exceptions (Leon et al, 1993; Leon et al, 1995; McCabe and Ricciardelli, 2004), pubertal timing effects have been observed in late (Baker et al, 2012; Graber et al, 1994; Harden et al, 2012; Hayward et al, 1997; Ohring et al, 2002; Oinonen and Bird, 2012) as well as young (Ackard and Peterson, 2001; Graber et al, 1994; Keski-Rahkonen et al, 2005; Ohring et al, 2002; Petersen et al, 1994; Reichborn-Kjennerud et al, 2004; Striegel-Moore et al, 2001; Tenconi et al, 2006; Zehr et al, 2007) and middle (Johansson and Ritzen, 2005) adulthood. Several studies were prospective and found that timing effects assessed during puberty persisted one to 30 years after initial assessment.…”
Section: Associations Between Pubertal Status Pubertal Timing and Ementioning
confidence: 99%
See 1 more Smart Citation
“…With some exceptions (Leon et al, 1993; Leon et al, 1995; McCabe and Ricciardelli, 2004), pubertal timing effects have been observed in late (Baker et al, 2012; Graber et al, 1994; Harden et al, 2012; Hayward et al, 1997; Ohring et al, 2002; Oinonen and Bird, 2012) as well as young (Ackard and Peterson, 2001; Graber et al, 1994; Keski-Rahkonen et al, 2005; Ohring et al, 2002; Petersen et al, 1994; Reichborn-Kjennerud et al, 2004; Striegel-Moore et al, 2001; Tenconi et al, 2006; Zehr et al, 2007) and middle (Johansson and Ritzen, 2005) adulthood. Several studies were prospective and found that timing effects assessed during puberty persisted one to 30 years after initial assessment.…”
Section: Associations Between Pubertal Status Pubertal Timing and Ementioning
confidence: 99%
“…While four studies found early maturers to be at increased risk for eating disorder symptoms into late adolescence/young adulthood (Domine et al, 2009; McCabe and Ricciardelli, 2004; Nielsen, 1985; Zehr et al, 2007), three studies failed to find an effect of early pubertal timing on eating disorder risk during these later time periods (Keski-Rahkonen et al, 2005; Leon et al, 1995; Reichborn-Kjennerud et al, 2004). Only one prospective study of pubertal status found persistence of effects (Baker et al, 2012) while others found no significant associations between advanced pubertal development at time 1 and later risk for eating disorders at time 2 (Keel et al, 1997; Ricciardelli and McCabe, 2003). …”
Section: Associations Between Pubertal Status Pubertal Timing and Ementioning
confidence: 99%
“…Pubertal onset is associated with increased risk for eating disorder-related behaviors in girls and with the developmental emergence of genetic risk for eating disorders (Baker, Thornton, Lichtenstein, & Bulik, 2012; Klump et al, 2003). To date, no study has tested whether early pubertal onset is associated with different trajectories for the development of binge eating and purging behavior.…”
Section: Risk Factors For Early Engagement In Binge Eating and Purgingmentioning
confidence: 99%
“…Self-report measures can be standardized by age within each sex to create an indicator of pubertal timing (e.g., Natsuaki, Biehl, & Ge, 2009). In the current article, we refer to these age-standardized ratings of body changes as “ stage-normative timing .” Stage-normative timing predicts substance use (Costello, Sung, Worthman, & Angold, 2007), disordered eating (Baker, Thornton, Lichtenstein, & Bulik, 2012), delinquency (Harden & Mendle, 2012), and depression (Natsuaki, Biehl, & Ge, 2009). Stage-normative measures are modestly correlated with physician ratings of Tanner stages and with pubertal hormones (Bonat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%